CURRENT SOIL STATE OF POPULATIONS OF SEDUM HYBRIDUM L. AND SEDUM EWERSII LEDEB. FOUND IN THE ZAILIY ALATAU (Eurasian Journal of Ecology, 2024)
The article describes the natural soil conditions of Sedum hybridum L. and Sedum ewersii Ledeb—populations area based on the results of field and laboratory soil studies of soils. Soil types, morphological features, chemical composition, nutrient elements, amount of humus, absorbed bases and salt composition, and mechanical composition of soils are determined. The following soil types were identified during field studies: Kokzhailau Gorge (population 1) – chernozem, Turgeni Gorge (population 2) – chernozem, near Kastek River (population 3) – chestnut soil. The humus content in the 0-80 cm layer of chernozem (population 1) of Kokzhailiau gorge is very high, ranging from 5.55-12.81%, the reaction of the soil medium is within pH 7.10-7.40, i.e. CO2 content ranges from 0.16 to 0.34. On chernozems of Turgeni gorge (population 2) humus content in 0-60 cm layer is very high, within 5.90-20.88%, reaction of soil medium within pH 6.15-7.07, amount of CO2 within 0.21-0.34.On chestnut soils near the Kastek River (population 3), the humus content in the 0-73 cm layer was in the range of 1.57-6.92%, the pH ranged from 7.13-8.23, i.e. it was alkaline, the CO2 content was in the range of 0.16 - 0.34. The composition of salts in the chernozems of the Kokzhailau gorge: CO3 - not detected; HCO3- - 0,24- 0,48 ; Cl- – 0.04; CO4- – 0,12-0,92; Sa+ – 0,29-0,49; Mg 2+ – 0,20-0,98; Na+ – 0,05-0,06; To+ – 0,05-0,23; The amount of salts is 0.060-0.083%. It was found that the soils of all 3 populations are not saline, since the amount of salts does not exceed the salinity limit.Keywords: population, soil, profile, humus, salt.